PERAN PEMERINTAH DALAM PENGEMBANGAN INOVASI TECHNOPARK DI KABUPATEN BANTAENG - Reski Elvira R; Fatmawati Fatmawati; Abdi Abdi (Program Magister Ilmu Administrasi Publik, Universitas Muhammadiyah Makassar, 2022)
This study aimed to explain the role of the government in developing technopark innovations in Bantaeng Regency. The identification process was carried out by documentation, interviews and direct observation through qualitative methods. The theory used by researcher in analyzing the government's role in developing technopark innovation was using the theory proposed by La Pas and Seo (2009) with data analysis techniques, namely data reduction, data presentation and conclusion making. The results of this study showed that the Government's Role in Developing Technopark Innovations in Bantaeng Regency which included 1) Needs and Solutions, 2) Production and Commercialization Development, 3) ICT Learning, 4) Market Creation and Regulation, was not yet optimal due to several related UPTDs. with the technopark not working properly as a result of the lack of human resources and the procurement of tools and materials that were not equivalent to the existing local government budget.